2022
DOI: 10.15587/1729-4061.2022.263041
|View full text |Cite
|
Sign up to set email alerts
|

Principle of the assessment of the readiness of motor transport enterprises for economic development based on a two-component methodological approach

Abstract: The object of this study is to assess the financial stability and readiness of motor transport enterprises for economic development. The proposed two-component methodological approach makes it possible to optimize the assessment of the readiness of enterprises for development based on the calculation of the integral indicator of investment sufficiency and the level of material cost. The proposed methodical approach was tested, which showed the low resource capacity of enterprises. The dynamics of the integral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In this study, in contrast to [2,3,10,11], the economic efficiency of technical development projects is determined using the net present value method, which, compared to profit or costs, more fully corresponds to modern market conditions. In comparison with work [5], this study showed that taking into account measures to update the production and technical base when updating the rolling stock significantly affects the efficiency of the development of the motor vehicle enterprise.…”
Section: Discussion Of Results Of Investigating the Technical Develop...mentioning
confidence: 87%
See 2 more Smart Citations
“…In this study, in contrast to [2,3,10,11], the economic efficiency of technical development projects is determined using the net present value method, which, compared to profit or costs, more fully corresponds to modern market conditions. In comparison with work [5], this study showed that taking into account measures to update the production and technical base when updating the rolling stock significantly affects the efficiency of the development of the motor vehicle enterprise.…”
Section: Discussion Of Results Of Investigating the Technical Develop...mentioning
confidence: 87%
“…Another shortcoming of this study is a superficial assessment of the availability of attracting investment and other resources during the implementation of technical development projects. However, this problem is studied in detail in other works, for example [4,5].…”
Section: Discussion Of Results Of Investigating the Technical Develop...mentioning
confidence: 99%
See 1 more Smart Citation